Microfluidic Synthesis of Barcode Particles for Multiplex Assays. Issue 2 (20th October 2014) - Zhao, Yuanjin; Cheng, Yao; Shang, Luoran; Wang, Jie; Xie, Zhuoying; Gu, Zhongze
<x xml:space="preserve">Abstract</x> The increasing use of high‐throughput assays in biomedical applications, including drug discovery and clinical diagnostics, demands effective strategies for multiplexing. One promising strategy is the use of barcode particles that encode information about their specific compositions and enable simple identification. Various encoding mechanisms, including spectroscopic, graphical, electronic, and physical encoding, have been proposed for the provision of sufficient identification codes for the barcode particles. These particles are synthesized in various ways. Microfluidics is an effective approach that has created exciting avenues of scientific research in barcode particle synthesis. The resultant particles have found important application in the detection of multiple biological species as they have properties of high flexibility, fast reaction times, less reagent consumption, and good repeatability. In this paper, research progress in the microfluidic synthesis of barcode particles for multiplex assays is discussed. After introducing the general developing strategies of the barcode particles, the focus is on studies of microfluidics, including their design, fabrication, and application in the generation of barcode particles. Applications of the achieved barcode particles in multiplex assays will be described and emphasized. The prospects for future development of these barcode particles are also presented.